miRNA-193b-5p Suppresses Pancreatic Cancer Cell Proliferation, Invasion, Epithelial Mesenchymal Transition, and Tumor Growth by Inhibiting eEF2K - Gurbuz, Nilgun; Kahraman, Nermin; Sonmez, Hafize E.; Mokhlis, Hamada Ahmed; Kosar, Pinar Aslan; Ozpolat, Bulent (Anti-Cancer Agents in Medicinal Chemistry, 2022)
Background: Pancreatic ductal adenocarcinoma (PDAC) is the 4th leading cause of cancer deaths in the US due to the lack of effective targeted therapeutics and extremely poor prognosis. Objective: The study aims to investigate the role of miR-193b and related signaling mechanisms in PDAC cell proliferation, invasion, and tumor growth. Methods: Using PDAC cell lines, we performed cell viability, colony formation, in vitro wound healing, and matrigel invasion assays following transfection with miR-193b mimic or control-miR. To identify potential downstream targets of miR-193b, we utilized miRNA-target prediction algorithms and investigated the regulation of eukaryotic elongation factor-2 kinase (eEF2K) and mitogen-activated protein kinase/extracellular signal-regulated kinase (MAPK/ERK) signaling pathways and mediators of epithelial mesenchymal transition (EMT). The role of miR-193b in PDAC tumorigenesis was evaluated in in vivo tumor growth of Panc-1 xenograft model in nude mice. Results: We found that miR-193b is under expressed in PDAC cells compared to corresponding normal pancreatic epithelial cells and demonstrated that ectopic expression of miR-193b reduced cell proliferation, migration, invasion, and EMT through downregulation of eEF2K signaling in PDAC cells. miR-193b expression led to increased expression of E-Cadherin and Claudin-1 while decreasing Snail and TCF8/ZEB1 expressions via eEF2K and MAPK/ERK axis. In vivo systemic injection of miR-193b using lipid-nanoparticles twice a week reduced tumor growth of Panc-1 xenografts and eEF2K expression in nude mice. Conclusions: Our findings suggest that miR-193b expression suppresses PDAC cell proliferation, migration, invasion, and EMT through inhibition of eEF2K/MAPK-ERK oncogenic axis and that miR-193b-based RNA therapy might be an effective therapeutic strategy to control the growth of PDAC.
Keywords: proliferation